Предмет: Алгебра,
автор: alya9422
Упростите выражение (a3 + b3)3 – (a3 – b3)3 – 2b9
ПОМОГИТЕ ПЛИЗ!!! СРОЧНО
Ответы
Автор ответа:
10
(a³+b³)³-(a³-b³)³-2b⁹= (a³+b³-a³+b³)(a⁶+2a³b³+b⁶+a⁶-b⁶+a⁶-2a³b³+b⁶)-2b⁹= 2b³(3a⁶+b⁶)-2b⁹= 6a⁶b³+2b⁹-2b⁹= 6a⁶b³
alya9422:
а откуда взялось а в 6 ???
Автор ответа:
15
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Русский язык,
автор: ТиМоФеЙ2012
Предмет: Українська мова,
автор: nastenkaslastenka24
Предмет: Математика,
автор: Andrewmedvedev
Предмет: Литература,
автор: berdygin001